Implementasi Kompres Hangat pada Pasien Nyeri Akut di Ruang Gincu 1 RSUD Indramayu - Nengsih Yulianingsih; Violin Jelita Tarahati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Introduction: acute postpartum pain is caused by physiological changes that occur in postpartum mothers such as degeneration and necrosis at the placenta, the return of the uterus to its pre-pregnant condition, and changes in the vulva and vagina, in which case postpartum mothers need knowledge in providing warm compress relaxation therapy to reduce the pain felt after childbirth. Purpose: This case study is to analyze the implementation of warm compresses on Mrs. K, postpartum pregnancy serotinous patient with a nursing diagnosis of acute pain in Gincu Room 1, Indramayu Regional Hospital. Method: The method in this writing uses a case study. Data collection uses nursing care process which includes assessment, diagnosis, intervention, implementation and evaluation. As well as NRS (Numerical Rating Scale) as a pain scale instrument. Results and Discussion: before the warm compress was applied, the pain scale was 9 (0-10) with a response to complaints of pain, the patient grimaced, said he had difficulty sleeping, the patient only focused on himself and did not follow orders. After 2 days of giving the warm compress for 15 minutes, there was a change in the scale pain becomes 5 (0-10) with the response to the patient's complaint of pain, the grimace has decreased, the patient can sleep, the patient can focus and follow orders well. Conclusion: based on the implementation of warm compresses that have been carried out on Mrs. For postpartum pregnancy serotinous patients with a nursing diagnosis of acute pain in the Gincu Room 1, Indramayu Regional Hospital, the problem of acute pain in the patient can be resolved and the patient's outcome target is achieved.